INTERSCHOLASTIC ATHLETIC - Juridi Kalalo; Melky Pangemanan; Augustinus Robin Butarbutar (STIKES Columbia Asia Medan, 2024)
Interscholastic athletics is a sports program held between schools, especially at the middle and high school levels. This program plays an important role in the physical, mental, and social development of students. This study examines the various benefits that students gain from participating in interscholastic athletic, including improved physical and mental health, better academic achievement, and character development through values such a teamwork, discipline, and leadership. Involvoment in sports activities also strengthens relationship with the community, creating a sense of community and identity among students. Thus, interscholastic athletic serves not only as a competitive arena but also as a valuable educational tool, supporting the holistic development of students in various aspects of their lives. This study confirms the importance of interscholastic athletic programs in the context of student education and character development.